De coleccionistas y numismáticos a historiadores profesionales: notas sobre los orígenes de la Junta de Historia y Numismática Americana - Buchbinder, Pablo (Historiografías, 2023)
As a contribution to the shaping of professionalization and institutionalization of history in Argentine, this article examines the origins of the American Numismatics and History Board, which was transformed in the National Academy of History in 1938. To that purpose we shall study its first publications and strategies to reconstruct the Argentinian historical heritage; second, we address its bonds with the state and the government; and next, the debates on the Argentinian past. The exam of its participation in the celebrations of the centennial of the May Revolution and the Independence shall also be object of attention.KeywordsHistoriography, professionalization, historical heritage, numismatics